TANGGUNG JAWAB ADMINISTRATIF TENAGA KESEHATAN DALAM PELAYANAN PUBLIK: PERSPEKTIF HUKUM KESEHATAN - Hotmaria Hertawaty Sijabat (CV. Adiba Aisha Amira, 2025)
In the context of public service, healthcare workers have administrative responsibilities that are an important aspect of health law. These responsibilities include compliance with regulations, medical record-keeping, protection of patient rights, and ethical and legal management of medical information. Good administration is a key pillar in the integration of healthcare systems, maintaining quality, and improving the accountability of healthcare professionals. Violations of administrative responsibilities can result in legal implications, including criminal, civil, or administrative sanctions. Therefore, legal education for healthcare workers is necessary to ensure they understand and perform their administrative duties properly, thereby providing optimal care while protecting themselves from future legal risks.